KAJIAN PERFORMA BOBOT PRASAPIH DOMBA GARUT DI UPTD-BPPTDK MARGAWATI GARUT (Study on the Performance of Preweaning Weight of Garut Sheep at UPTD-BPPTDK Margawati Garut) - Ayu Kamila Haya; Asep Anang; Denie Heriyadi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
The development of local genetic resources is important to meet the need of high demand of lamb meat in Indonesia, especially in West Java, through the selection of superior breeds of Garut sheep. The selection has to be initiated by studying the Garut sheep performances to determine the environmental factors affecting the preweaning performances of the sheep and involving those factors in the analysis of genetic parameters. The study was held on the Unit Pelayanan Teknis Dasar Balai Pengembangan Perbibitan Ternak Domba dan Kambing (UPTD-BPPTDK) Margawati Garut from August 21st to September 18th, 2019. The purpose of this experiment was to study the effect of sex and litter size on preweaning weight, i.e birth weight, weight on 30, 60, 90 days, and weaning weight (100 days). The traits were analyzed on 6.349 heads, 3.214 rams, and 3.135 ewes, from 2012 to 2019 using the General Linear Model (GLM) and Duncan multiple range test of SAS 9.0 software. The fixed effects used in the analysis were the sex and the birth type. The results showed that the performance of Garut Sheep based on the preweaning weight was affected significantly (P<0.05) by the sex, with the average of birth weight, 30, 60, 90 days weight and weaning weight (100 days) were 2.46 kg, 5.64 kg, 7.73 kg, 9.92 kg, 10.97 kg (rams) and 2.33 kg, 5.42 kg, 7.34 kg, 9.36 kg, and 10.28 kg (ewes). The pre-weaning weight was also significantly affected (P<0.05) by the birth type, in which the average of birth weight, 30, 60, 90 days weight and weaning weight (100 days) were 2.96 kg, 6.49 kg, 8.98 kg, 11.29 kg, 12.52 kg (single), 2.25 kg, 5.09 kg, 6.78 kg, 8.71 kg, 9.52 kg (twin), 1.79 kg, 4.62 kg, 6.24 kg, 8.09 kg, 8.92 kg (triplet), 1.54 kg, 4.53 kg, 5.89 kg, 7.15 kg, 8.03 kg (quadruplet), and 1.51 kg, 3.84 kg, 5.23 kg, 6.58 kg, 7.15 kg (quintuplet). Based on the results, preweaning weight must be corrected by the sex and the birth type before the genetic parameters are analyzed to avoid bias of selection results.